THE IMPACT OF ATTITUDE CHANGE FOR CLEANLINESS AMONG LOW COST FLAT RESIDENTS TOWARDS QUALITY OF LIFE IN JOHOR BAHRU, MALAYSIA - Mohd Hafizal Ishak; Nurul Syamimi Roslee; Azlina Md. Yassin (International Journal of Property Sciences (E-ISSN: 2229-8568), 2024)
The primary cause of cleaning problems in low-cost flats is the attitude of the residents, who are frequently perceived as disliking their shared accountability and dedication to maintaining their dwelling zones. Hence, these attitudes will impact low-cost flats’ quality of life (QOL). However, the relationship and effects of a change in attitude toward cleanliness from a property management perspective have received less attention in the literature. This study is conducted to determine attitude change factors for cleanliness among low-cost flat residents and to analyse the impact of attitude change factors towards resident’s quality of life (QOL) near Johor Bahru. The quantitative method was used through a questionnaire survey from 100 respondents among low-cost residents. Descriptive analysis, factors analysis and correlation analyses were used for the data. The result shows that cognitive biases and belief formation are the top attitude change factors among the residents. The correlation between attitude change factors and QOL showed a strong correlation between cognitive and behavioural elements. This result can be a basis for further exploration of the change in the cleanliness attitude of low-cost residents.